Establishing a Research Information System as Part of an Integrated Approach to Information Management: Best Practice at the Karlsruhe Institute of Technology (KIT) - Scholze, Frank; Maier, Jan (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2012)
The Karlsruhe Institute of Technology (KIT) is one of the largest research and higher education organisations in the world focusing on engineering and natural sciences. At present KIT, under the chairmanship of its executive board, is installing an extensive current research information system (CRIS) covering all institutes and facilities of the organisation. The assumption underlying the project is that a consistent overview of research performance has become fundamental for the international competitiveness of research institutions and is increasingly important for strategic decisions at the executive level. Ultimately, it also leads to better data and control in rankings at higher education assessments. The new research information system systematically maps all of KIT’s processes and instruments to obtain, connect, present and utilise the research metadata of active researchers. This reduces the documentation workload for researchers, for the executive level and central units such as the library, and at the same time allows for and facilitates an overall view and the aggregation and visualisation of research metadata. Our vision is to build a federally structured network of systems that gathers information on KIT’s publications, research competence, research projects, patents and technological offers by retrieving data from external and internal sources as well as directly from the researchers. The network facilitates linking and aggregating of data and provides unique identifiers for individual researchers and organizational units. With its consistent data model the research information system also fosters the organisational development of KIT, which was formed in 2009 by the merger of a university and a national research centre. The researchers and their activities are at the core of the research information system. The system substantially reduces their administrative burden in documenting project information and publications. Automatic data import from external online sources and repositories has the big advantage that publication data are acquired and validated only once and can be used subsequently for manifold purposes such as websites, CVs, publication lists and reference management software. Due to the complexity of workflows, internal and external sources and the organisational infrastructure that is required for such an implementation, KIT has chosen a commercial software solution (by AVEDAS AG) as the basic installation, and in cooperation with AVEDAS will expand it and adjust it to a tailor-made system that covers the entire KIT publication and research life cycle. The CRIS at KIT is part of a larger integrated and service-oriented approach to information management (Karlsruhe Integrated Information Management — KIM).